Deforestation in a Ghanaian Rural Community - Dei, George S. (Anthropologica, 2022)
The case study examines the processes of deforestation in a Ghanaian rural community. The paper discusses the interrelated socio-economic, political, ecological and historical factors that account for the problem of deforestation. It is argued that knowledge of such micro-level processes of tree cutting in rural communities today may perhaps help provide some understanding or insights into the problem of deforestation and guide the search for its general solutions.